Lifestyle risk factors for ischemic stroke and transient ischemic attack in young adults in the stroke in Young Fabry Patients study - Sarnowski, Bettina von; Putaala, Jukka; Grittner, Ulrike; Gaertner, Beate; Schminke, Ulf; Curtze, Sami; Huber, Roman; Tanislav, Christian; Lichy, Christoph; Demarin, Vida; Basic-Kes, Vanja; Ringelstein, E. Bernd; et al. (Stroke, 2013)
Background and Purpose: Although many stroke patients are young or middle-aged, risk factor profiles in these age groups are poorly understood. - Methods: The Stroke in Young Fabry Patients (sifap1) study prospectively recruited a large multinational European cohort of patients with cerebrovascular events aged 18 to 55 years to establish their prevalence of Fabry disease. In a secondary analysis of patients with ischemic stroke or transient ischemic attack, we studied age- and sex-specific prevalences of various risk factors. - Results: Among 4467 patients (median age, 47 years; interquartile range, 40-51), the most frequent well-documented and modifiable risk factors were smoking (55.5%), physical inactivity (48.2%), arterial hypertension (46.6%), dyslipidemia (34.9%), and obesity (22.3%). Modifiable less well-documented or potentially modifiable risk factors like high-risk alcohol consumption (33.0%) and short sleep duration (20.6%) were more frequent in men, and migraine (26.5%) was more frequent in women. Women were more often physically inactive, most pronouncedly at ages <35 years (18-24: 38.2%; 25-34: 51.7%), and had high proportions of abdominal obesity at age 25 years or older (74%). Physical inactivity, arterial hypertension, dyslipidemia, obesity, and diabetes mellitus increased with age. - Conclusions: In this large European cohort of young patients with acute ischemic cerebrovascular events, modifiable risk factors were highly prevalent, particularly in men and older patients. These data emphasize the need for vigorous primary and secondary prevention measures already in young populations targeting modifiable lifestyle vascular risk factors.
Originally published 13 Nov 2012
Gesehen am 16.09.2021